The effects of stocking rate and level of winter supplementation on pregnancy rates in spring calving cows in the Kansas Flint Hills - L.R. Sprott; L.R. Corah; G.H. Kiracofe; Clenton E. Owensby (Kansas Agricultural Experiment Station Research Reports, 1981)
Pregnancy rates the first 40 days of breeding were lower in cows stocked at less than 6 acres/AU than in those allowed more grazing acres. Supplementation rate during the last 100 days of gestation had little effect on pregnancy rates. Thin cows that had weaned their firs calf had lowest pregnancy rates.
Keywords: Cattlemen' s Day; 1981; Report of progress (Kansas State University. Agricultural Experiment Station); 394; Beef; Stocking rate; Pregnancy rates